The Altadir Method as a management teaching instrument in nursing - Baldissera, Vanessa Denardi Antoniassi; Góes, Herbert Leopoldo de Freitas (Investigación y Educación en Enfermería, 2012)
<!– [if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]–><!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–> This paper presents the Altadir Method of Popular Planning (MAPP), which is considered an effective tool for nursing management teaching and learning. When using traditional knowledge-transfer centered methods, the teaching on this subject does not arouse the same interest as technical education. The MAPP is a powerful planning tool for students who are finishing their education process, as it provides theoretical and practical experiences similar to what students will be confronted with later as professionals.